Economic Empowerment Model In Improving The Welfare Of Mualaf (Case Study Of The Muallaf Center Indonesia Care Regional Medan) - Sitompul, Humaidi; Rokan, Mustapa Khamal; Nasution, Muhammad Lathief Ilhamy (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to determine the programs carried out by the Medan Regional Center for Indonesian Mualaf Care (MCIP) in empowering the economy of converts through the management of zakat, infaq, shadaqoh (ZIS). The type of research used in this research is qualitative with data triangulation analysis, namely by combining data from various sources, methods or theories. Type of data collection was carried out using interview techniques, observation, documentation with the research object of Muslim converts who were empowered by the Indonesian Center for Muslim Concern (MCIP) institution. The results of the research show that the Medan Regional Center for Indonesian Muslim Concerns (MCIP) manages zakat and empowers the economy of converts through the zakat given. Empowerment is realized through programs such as Life Skills Training, Basic Food Assistance and Funding for Muslim MSMEs. Good economic empowerment indicates that mustahiq also have good economic qualities. This is due to changes in the mindset of converts who are increasingly developing regarding efforts to improve their standard of living to be better than before. Therefore, economic empowerment can increase the welfare, income and independence of converts.